(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
The ultrasound machine generates images to examine various parts of the human body. It emits high-frequency sound waves that are reflected off bodily structures, and a computer receives these reflected waves to create images. Unlike X-rays or CT scans, ultrasound does not utilize ionizing radiation. Ultrasound has gained popularity due to its widespread availability and the ability of modern devices to produce high-resolution images, offering exceptional clarity, which in turn provides precision, accuracy, sensitivity, and specificity. A major advantage of ultrasound is that it allows frequent examinations without causing harm to the patient, as it does not emit radiation. As the name suggests, ultrasound typically refers to high-frequency sound waves. These waves pass through body tissues and are converted into electrical signals. The accuracy of ultrasound diagnostics depends on the operator’s expertise in handling the equipment, selecting the appropriate probe, identifying artifacts, and interpreting the results. There are several ultrasound techniques, including A-mode, B-mode, M-mode, Doppler, contrast-enhanced ultrasound, and other techniques. In medicine, ultrasound is also used for interventional procedures, such as guiding biopsies. Ultrasound can visualize nearly all organ systems within the human body without causing harm to the patient, making it the gold standard in diagnostic imaging.